Chinese Belt And Road Initiative In The Countries Of The Gulf Cooperation Council - Aghavni Harutyunyan (Banber Arevelagitut'yan Instituti, 2025)
China's relations with the Gulf Cooperation Council (GCC) countries have expanded significantly in recent years, especially in the areas of geopolitics, economics, trade, finance, banking, infrastructure, energy and security. China is deepening its economic cooperation with the GCC monarchies through the China-Arab Cooperation Forum (CASCF) and the China-GCC Framework Agreement. A mechanism that can strengthen trade relations is the FTA between China and the GCC. The Chinese New Silk Road Initiative (NSRI) was accepted by all GCC countries that became members or perspective members of the Chinese-led Asian Infrastructure Investment Bank (AIIB). The NSRI project called "Industrial Park - Connecting ports, Two- Wheel and Two-Wing Approach" would provide the basis for consolidating China-built industrial parks in key cities of the GCC with regional ports to create business clusters, increase trade flows, and connect supply chains across the region. The future of relations between China and the GCC oil-producing countries will be based on strong, less fluid building blocks, which has facilitated alignment of the NSRI with the national development concepts of the GCC countries. All, are designed to diversify their economies from a single-resource rentier model to a post-oil model, with the necessary transition to manage their dependence on foreign labor, public sector employment and heavily subsidized utilities.